Executive summary of 'Cultural values in financial services advertising: a cross-cultural study of magazine ads in the US and Korea'. Issue 5 (19th August 2014) - Beal, Brian; Martin, Charles; Fall, TansyMarie
<x content-type="archive" xml:space="preserve">Abstract</x>